Some di- and triterpenes of Wedelia urticaefolia (Bl.) (Asteraceae) - Phi Phung et al, Nguyen Kim (Vietnam Journal of Chemistry, 2014)
Wedelia urticaefolia Bl. DC. (Vietnamese name Sơn cúc nhám) has not yet been chemically studied. From leaves of this plant, four compounds were isolated: phytol (1), 3β-O-acetyl-b-amyrin (2), 3-O-tetradecanoylurs-12-ene-16β-ol (3), ent-kaur-16-ene-19-oic acid (4) and from the flowers, three compounds were isolated: b-amyrin (5), stigmasterol (6) and 3-O-tetradecanoylurs-12-ene-16β-ol (3). Their chemical structures were established by spectroscopic analysis.